2023
DOI: 10.3389/fimmu.2023.1126034
|View full text |Cite
|
Sign up to set email alerts
|

Glycan masking in vaccine design: Targets, immunogens and applications

Abstract: Glycan masking is a novel technique in reverse vaccinology in which sugar chains (glycans) are added on the surface of immunogen candidates to hide regions of low interest and thus focus the immune system on highly therapeutic epitopes. This shielding strategy is inspired by viruses such as influenza and HIV, which are able to escape the immune system by incorporating additional glycosylation and preventing the binding of therapeutic antibodies. Interestingly, the glycan masking technique is mainly used in vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…By forming a dense outer shell that covers the immunogenic protein surface, viruses such as HIV-1, influenza virus, and coronaviruses can effectively mask themselves from the immune system ( 20 22 ). This glycan masking approach has been adopted in the field of vaccinology to conceal regions of low importance and redirect the immune response towards highly therapeutic epitopes to ultimately achieve a more focused or broadened immune response ( 23 ). Research has shown that glycan masking of certain non-neutralizing epitopes on antigens of viruses such as HIV, the influenza virus, and the Middle East respiratory syndrome coronavirus (MERS-CoV) can effectively enhance neutralizing antibodies ( 24 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…By forming a dense outer shell that covers the immunogenic protein surface, viruses such as HIV-1, influenza virus, and coronaviruses can effectively mask themselves from the immune system ( 20 22 ). This glycan masking approach has been adopted in the field of vaccinology to conceal regions of low importance and redirect the immune response towards highly therapeutic epitopes to ultimately achieve a more focused or broadened immune response ( 23 ). Research has shown that glycan masking of certain non-neutralizing epitopes on antigens of viruses such as HIV, the influenza virus, and the Middle East respiratory syndrome coronavirus (MERS-CoV) can effectively enhance neutralizing antibodies ( 24 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…These immunogens have shown promise in preclinical animal models as well as humans since they generated the intended epitope-specific B cell responses 15,26,3136 . Immunofocusing strategies, including glycan masking 37 and protein resurface engineering 16,3842 , have also been employed to direct B cell responses towards desired bnAb epitopes and away from off-target sites. Among various immunogen templates, native-like Env trimers that mimic the conformation of the pre-fusion spike on the virion surface 4245 have been shown to elicit autologous nAb responses 4648 .…”
Section: Introductionmentioning
confidence: 99%
“…Garrity et al [ 3 ] introduced this process in relation to the human immunodeficiency virus (HIV) and coined it decotope, or immune decoy epitopes. This process was defined as a shift from immunodominant epitopes to a limited pool of neutralizing antibodies providing low protection [ 3 , 4 ]. Here, we argue against this notion and present several ways in which the immune system can still mount a response against mutated variants.…”
Section: Introductionmentioning
confidence: 99%
“…Glycan masking is also implicated in this immune shifting, or a shift in the immune response away from specific epitopes while focusing on other epitopes to decrease the extent of off-target antibody production. This also has been linked with reduced ADE activity and increased B cell regulation and testing [ 4 ]. However, there are some downsides to glycan masking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation